Classification of Student Rental Housing Around the Universitas PGRI Yogyakarta - Brema Heva Faralita; Davito Bagus Hernandhi; Miftachudin; Rizky Agus Rinaldi; Nur Aini (Yayasan Putra Adi Dharma, 2024)
Several universities in Indonesia usually provide rental housing facilities for their students to accommodate their temporary housing needs during the study period, which is usually in the form of dormitories or flats. Rental housing is one of the needs that students need while studying at a college or university, especially for students who come from outside the area where the college is located. However, because the number of students is not comparable to the rental housing capacity provided by the campus, students have to look for alternative housing in the area around the campus. Therefore, many private sectors have emerged in areas around campus that provide various types of housing for students. This research aims to analyze the typology of student housing around the PGRI Yogayakarta University campus. This research uses a qualitative descriptive method with direct observation to collect, analyze and conclude the necessary data and information related to the typology of student housing around the PGRI Yogyakarta University area.